Analisis Modal Kerja Terhadap Profitabilitas Perusahaan Sub Sektor Kimia di Indeks Saham Syariah - Nasya Ariesta Firdaus; Leni Nur Pratiwi; Setiawan Setiawan (Journal of Applied Islamic Economics and Finance, 2022)
This study aims to determine the relationship between Average Age of Inventory (AAI), Average Collection Period (ACP), Average Payment Period (APP) and Firm Size (FSz) variables on the Return On Asset (ROA) variable. The object of research is a chemical sub-sector company listed on Sharia Stock Index for the 2016-2020 period. The data analysis method used was multiple linear regression with panel data using EViews 9 software. The results showed that partially AAI and ACP variables had a negative and insignificant effect on ROA, while APP and FSz had a negative and insignificant effect on ROA. Simultaneously the variables AAI, ACP, APP and FSz have a positive and significant effect on ROA.